Monitorization of Timed Up and Go Phases in Elderly. (3rd April 2021) - Lima, Miguel; Rodrigues, Sílvia Rocha; Bezerra, Pedro; Rodrigues, Luís Paulo; Cancela, José Maria
Abstract: Aims: to characterize functional mobility during timed "Up and Go" (TUG) test using Wiva ® science sensor and to identify which parameter of TUG test best correlates with health-related outcomes in elderly. Methods: 1598 participants (71.53 ± 4.99 y, 64.1% women) were recruited. The body mass index (BMI), muscle strength, health status, and all TUG phases (sit-to-stand, gait-to-go, turning, gait-return, and stand-to-sit) were evaluated. 5-TUG performance-group scores are reported for the <20th; 20–40th, 40–60th, 60–80th, 80–100th percentiles, as there is no health standard cutoff for Portuguese elderly. The Pearson's correlations were assessed between variables ( p  < 0.05). Results: The best TUG performers (<20th) presented better results than the other groups for all tests, with the exception of the Turning phase. Both gait, sit-to-stand and stand-to-sit were inversely correlated with health status and muscle strength, and positively correlated with BMI. Conclusions: All phases of TUG test are an important tool to assess functional mobility, providing complementary data for clinical settings in elderly population.